Correlation Analysis of Postural Balance in Roller Skate Athletes Between Single Leg Stand and Tandem StandCorrelation Analysis of Postural Balance in Roller Skate Athletes Between Single Leg Stand and Tandem Stand - Arti, Widi; Zubairi Abdillah, Okky; Suprianto, Suprianto; Hanum, Sri Mukhodim Farida (Universitas Negeri Semarang, 2025)
Introduction: Postural balance is a crucial component in the performance of roller skate athletes, especially in maintaining stability during dynamic movements. Objectives: This study aimed to analyze the relationship between two postural balance assessment methods: single leg stands and tandem stands, among roller skate athletes aged 10 to 15 years. Method: The study involved 15 athletes selected purposively. Balance data were collected using the single-leg stand and tandem stand tests and analyzed with the Shapiro-Wilk normality test and Pearson correlation test. Result: The results showed that both variables were normally distributed and had a very strong and significant correlation (r = 0.934; p < 0.001). These findings indicate that better balance performance in one method tends to reflect better performance in the other. This confirms that both methods can represent the postural balance ability of roller skate athletes. Conclusion: The study concludes that there is a very strong positive correlation between single leg stand and tandem stand, which can serve as a basis for evaluating and developing balance training programs for roller skate athletes.